APPLICATION OF CURVED PSEUDO-ELASTIC IMPEDANCE (CPEI) AND PSEUDO-ELASTIC IMPEDANCE FOR LITHOLOGY (PEIL) FOR RESERVOIR CHARACTERIZATION ON AK FIELD - KHO NIM: 12314034 , ALDO
Rock Physics Template (RPT) accompanied by AVO inversion data can be used to assist in reservoir characterization. In the RPT domain, extended elastic impedance (EEI) can have a correlation with physical properties of rock. Among them include fluid saturation and rock stiffness. However, the EEI trend is linear while the trend of fluid saturation is generally non-linear and curved. Therefore, the Curved Pseudo-Elastic Impedance (CPEI) attribute is used which can better describe curved and non-linear fluid trends. In addition, the Pseudo-Elastic Impedance for Lithology (PEIL) attribute is used to describe the trend of rock stiffness. The advantage of these two attributes is that they can be formed from seismic inversion data. The formation of these two attributes is done by first forming a brine-saturated sandstone model in the RPT domain. Then the CPEI value is determined by the deviation of the Brine-saturated sandstone curve in the RPT domain. PEIL value is obtained from the formation of pseudo-elastic impedance (PEI) which follows the linear trend of fluid, then the deviation of this trend is calculated as PEIL value. Both of these attributes are then applied to field data which are log data from three wells and volume data of Rp and Rs on the AK field. After the two CPEI and PEIL attributes were applied to the AK field, it was found that the PEIL attribute cannot be used for reservoir characterization due to similarities with AI. Whereas by applying the CPEI attribute it was found that the distribution of hydrocarbons in the AK field was scattered in the eastern part of the field. The most hydrocarbon accumulation is found in the middle part of the AK field because of its higher elevation.